National Health Service
1945-08-02 1945 1940s 5 pages -4- Sale and Purchase of Practices The White Paper proposal on this matter was not definite but it pointed out that "the abolition would, however, involve great practical difficulty and is not essential to the working of the new service now proposed." It was also stated "the creation of health centres would meanwhile do a great deal to limit the scope of the present system. The centres would afford a wide opportunity to young doctors to enter their profession without financial burdens." The latest suggestion of the Ministers is that the Government do not propose to make any alteration in the present custom in the forthcoming health services bill but they propose that a full enquiry into the whole question should be instituted by a committee appointed for that purpose after the new service has come into operation and experience of its working has been gained. In the meantime the Government are considering how they can help doctors returning from the forces to acquire practices. It will be seen therefore that the provision of health centres has an important bearing on this question of sale and purchase of practices. Having regard to the difficulties created by the sale and purchase of practices, we think that this should be abolished. Remuneration The White Paper proposal was that practitioners participating in separate practice in the new service would be normally remunerated on a capitation basis though other methods would be considered if desired by the practitioners themselves. For group practice in health centres, remuneration would be by salary or similar alternative. The new suggestion is that the method of remuneration in separate general practice is to be by capitation but the views of the profession would be welcomed on the desirability of having some basic part salary over and above which the rest of the remuneration would be by capitation. The same method is suggested in respect of Health Centres i.e. basic part salary with the remaining aggregate income of the Centre to be shared out by the occupants themselves under a partnership agreement. No provision appears to be made for allowing a doctor to receive full time salary if he chooses. Having regard to the claim by the doctors that they should be free in practically everything, it does not seem unreasonable to suggest that a doctor should be free to accept a full time salary if he so desires. The 100% Issue The Ministers at the interview on the 8th March indicated that there was no danger to the 100% issue and that the scheme would apply to every member of the population. Private practice is of course also to be allowed so that a person who chooses can pay for private service. The General Council have not objected to that but it was laid down that there must be definite safeguards to secure that such private patients would not obtain preference or priority over public patients and that the public service should if anything be superior to private practice. The Ministers have not dissented from the General Council view. The B.M.A. regard the 100% issue as one for Parliament to decide but they say ample safeguards should be introduced so that any member of the community whatever his income should be able to obtain medical service in part or in whole privately, as for example, by "grant in aid provision". By this is meant presumably that a person who so desires can secure a return of his contributions 292/847/3/44